2007
DOI: 10.1038/sj.emboj.7601953
|View full text |Cite
|
Sign up to set email alerts
|

Lipids revert inert Aβ amyloid fibrils to neurotoxic protofibrils that affect learning in mice

Abstract: Although soluble oligomeric and protofibrillar assemblies of Aβ-amyloid peptide cause synaptotoxicity and potentially contribute to Alzheimer's disease (AD), the role of mature Aβ-fibrils in the amyloid plaques remains controversial. A widely held view in the field suggests that the fibrillization reaction proceeds ‘forward' in a near-irreversible manner from the monomeric Aβ peptide through toxic protofibrillar intermediates, which subsequently mature into biologically inert amyloid fibrils that are found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

25
250
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(276 citation statements)
references
References 50 publications
25
250
0
1
Order By: Relevance
“…These data identify microglial MVs as an endogenous source of lipids able to shift the equilibrium toward toxic Ab species. This conclusion is in complete agreement with previous evidence that brain membrane lipids, including phosho-and (glycol)sphingolipids, favor formation of soluble forms, either promoting solubilization of inert fibrils, 13 or hindering their conversion to insoluble fibrils. 14 Interestingly, exosomes released by neurons have been found to promote rather than reduce Ab fibrillogenesis, 40 thus indicating that lipid composition of different EMVs generated by distinct cell types may have opposite effects on Ab extracellular assembly.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These data identify microglial MVs as an endogenous source of lipids able to shift the equilibrium toward toxic Ab species. This conclusion is in complete agreement with previous evidence that brain membrane lipids, including phosho-and (glycol)sphingolipids, favor formation of soluble forms, either promoting solubilization of inert fibrils, 13 or hindering their conversion to insoluble fibrils. 14 Interestingly, exosomes released by neurons have been found to promote rather than reduce Ab fibrillogenesis, 40 thus indicating that lipid composition of different EMVs generated by distinct cell types may have opposite effects on Ab extracellular assembly.…”
Section: Discussionsupporting
confidence: 81%
“…The evidence that natural lipids may shift the equilibrium between insoluble and soluble Ab toward highly toxic soluble species 13,34 prompted us to test whether MVs shed from microglial cells may promote Ab neurotoxicity. Ab 1-42 (4 mM) dissolved in dimethyl sulfoxide (DMSO) was incubated overnight with MVs derived from rat primary microglia (1 mg/100 ml) at 37 1C in neuronal medium and subsequently exposed to cultured hippocampal neurons for 1 h. Overnight pre-incubation of Ab 1-42 with MVs yielded a neurotoxic mixture that significantly increased the percentage of dead neurons, as assessed 24 h later by propidium iodide (PI) and calcein staining (Figures 1a and b; number of experiments ¼ 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observations of ring-like structures formed from α-synuclein and prefibrillar assemblies of other amyloid-like systems, along with membrane leakage in the presence of prefibrillar oligomers, have led to the hypothesis of membrane pore formation, membrane thinning, and membrane destabilization by prefibrillar oligomers (8,9,12,34,35). In addition it has been shown that lipid-induced depolymerization of nontoxic Aβ fibrils leads to formation of so-called "reverse oligomers" that are cytotoxic, akin to the oligomers formed de novo during fibril assembly (36). Membrane-induced fibril depolymerization and membrane destabilization associated with fibril growth on lipid bilayers have also been proposed as alternative mechanisms of amyloid-mediated cytotoxicity (11, 13, 15).…”
Section: Discussionmentioning
confidence: 99%